Differences in metacognition between multiple sclerosis phenotypes: cognitive impairment and fatigue are key factors - Coll-Martinez, Clàudia; Salavedra-Pont, Judit; Buxó, Maria; Quintana, Ester; Quiroga-Varela, Ana; Robles-Cedeño, René; Puig, Marc; Álvarez-Bravo, Gary; Ramió-Torrentà, Lluís; Gich, Jordi (Frontiers in Psychology, 2023)
Background: Cognitive impairment is present in 40-65% of patients with multiple sclerosis (pwMS). Objectively measured cognitive performance often does not match patients' subjective perception of their own performance. Objective: We aimed to compare cognitive performance and subjective perception of cognitive deficits between pwMS and healthy controls (HC), as well as accuracy of subjective perception. Methods: Fifty-four HC and 112 pwMS (relapsing-remitting, RRMS, and progressive, PMS) underwent neuropsychological evaluation and completed perceived deficit, fatigue and anxietydepression scales. Participants were classified according to their consistency between subjective self-This is a provisional file, not the final typeset article evaluation of cognitive abilities and objective cognitive performance to assess the accuracy. Regression models were used to compare cognitive performance between groups and to explore factors explaining inaccuracy in the estimation of cognitive performance. Results: PMS showed greater and more widespread cognitive differences with HC than RRMS. No differences were found between pwMS and HC in the perception of deficit. PMS had higher ratios of overestimators. In explaining inaccuracy, fatigue and cognitive preservation were found to be risk factors for underestimation whereas physical disability and cognitive impairment were risk factors for overestimation.PwMS have metacognitive knowledge impairments. This study provides new information about metacognition, data on the prevalence of impairments over a relatively large sample of PwMS, as well as new insights about factors explaining it. Anosognosia, related to cognitive impairment, may be present in pwMS. Fatigue is a key factor in underestimating cognition.